Rede de afeto e memórias: uma análise de conteúdo das dedicatórias manuscritas entre Rachel de Queiroz e Manuel Bandeira - Bastos, Ana Wanessa Barroso (2024)
The universe of sociability networks of intellectuals of Brazilian literature is often reflected in the domain of their private libraries, considering that bibliographic collections represent an extension of individuals, having much to say about the way of life and interpersonal relationships of their original owners. Considering that the handwritten dedications, understood as marks of the book's provenance, constitute a valuable source and information in evidence to understand the history of those who write and receive them, the interest arose in investigating the dedications contained in the copies of books in the collections of Rachel de Queiroz and Manuel Bandeira.The proposed research has as general objective to analyze the content of the handwritten dedications between Rachel de Queiroz and Manuel Bandeira and as specific objectives to identify the copies of books dedicated among the writers; collect, document and map handwritten dedications; and to investigate the interpersonal and professional relationship between these authors, in order to verify patterns, themes and messages present in them. This is a documentary research, qualitative in nature and exploratory in nature. The content analysis of these handwritten dedications allows the interpretation of the messages contained, seeking to understand the networks of affection and memory present in the messages and the relationship between these writers, reflected in their literary objects. Through the analysis of the 23 dedications found, 21 of which were from Bandeira to Rachel and two from Rachel to Bandeira, it is possible to find patterns of style and aesthetics in Bandeira's communication marked by simplicity with depth, since the writer used a colloquial language, however loaded with meanings and intensity. In a complementary way, the patterns adopted by Rachel in her dedications express the colloquialism, simplicity and regionalism, characteristic of rachelian writing. It is concluded that the poet Manuel Bandeira was the most assiduous dedicator in the works of the collection of the writer Rachel de Queiroz, being evident in the dedications analyzed the intertwining of the affective and poetic dimensions that demonstrates personal and professional proximity, friendship, respect and mutual admiration between the literati.